Capital requirements and bank behaviour: empirical evidence for Switzerland - Bertrand Rime (Swiss National Bank, Study Center Gerzensee, 2000)
In recent years, regulators have increased their focus on the capital adequacy of banking institutions to enhance the stability of the financial system. The purpose of the present paper is to shed some light on whether and how Swiss Banks react to constraints placed by the regulator on their capital. Building on previous work by Shrieves and Dahl (1992), we use a simultaneous equations model to analyse adjustments in capital and risk at Swiss banks, when those approach the minimum regulatory capital level. Our results indicate that regulatory pressure induce banks to increase their capital, but does not affect the level of risk.
Keywords: G21; G28; 330; Risk-based capital; Capital ratios; Portfolio risk; Bank; Basler Akkord; Schweiz